Gene-associated single nucleotide polymorphism (SNP) in cinnamate 4-hydroxylase (C4H) and cinnamyl alcohol dehydrogenase (CAD) genes from acacia mangium superbulk trees* - Pang Shek, Shek Ling; Ismail, Jusoh; Tchin Boon, Ling; Ho Wei, Wei Seng (Asian Network for Scientific Information, 2011)
Candidate-gene-based association study which involves the identification of causative Single Nucleotide Polymorphisms (SNPs) for excellent traits has been proposed as a promising approach to dissect complex traits in forest trees. Hence, the goal of this study was to identify the genetic association among SNPs from Cinnamate 4-Hydroxylase (C4H) and Cinnamyl Alcohol Dehydrogenase (CAD) genes and an array of wood properties namely, specific gravity, wood density, fiber-length, cell wall thickness and microfibril angle from Acacia mangium Superbulk trees. Sequence variations within these two genes in 12 A. mangium Superbulk trees were examined and wood properties were measured. The data obtained was tested using General Linear Model (GLM) within TASSEL software. Two SNPs were identified in the exon of C4H, of which all the SNPs caused nonsynonymous mutations whereas five SNPs were identified in the CAD exons along with one deletion mutation. In addition, two SNPs were also identified in the CAD introns. Variation in these two lignin biosynthesis genes might change the structural, functional or biochemical properties of the enzyme being produced, and therefore possibly lead to changes in phenotypic characteristic of the trees. The genetic association study also revealed that SNPs in CAD gene do associate with the wood density, specific gravity and cell wall thickness (p<0.05). However, no significant results were obtained for SNPs in C4H gene with wood properties studied. Thickening of cell wall is affected by the arrangement of biopolymer aggregates which comprise of cellulose, hemicellulose and lignin. Results indicated that SNP in CAD gene might alter the lignin biosynthesis and thus lead to changes in phenotypic characteristics of the trees. Overall, the study has demonstrated that SNP is very useful in association genetic study to identify Quantitative Trait Nucleotide (QTN) which then leads to Gene-assisted Selection (GAS) in the tree breeding programme.